Optimizing The Role Of Islamic Religious Education Teachers In Finding The Practice Of Madrasah Students' Religious Values - Taufiq, Taufiq; Fanani, Ahmad Aziz; Mashuri, Imam (Al-Mudarris, 2024)
This research aims to analyze optimizing the role of Islamic religious education teachers in fostering the practice of religious values for madrasah students. This research uses a qualitative case study approach. The research subjects were the Head of the Madrasah, Deputy Head of Curriculum, Deputy Head of Student Affairs, Teachers, and Students. Data collection techniques use interview observation and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The research results show that the role of PAI teachers is very significant in shaping students' religious character. PAI teachers are role models in behavior and interaction and provide intensive guidance in daily religious activities at the madrasah. The practice of religious values such as congregational prayers, reading the Koran, and participating in other religious activities is taught and supervised consistently by PAI teachers. Challenges faced include limited time and resources and differences in levels of religious understanding among students. However, with the right strategies, such as strengthening communication with parents, continuous training for teachers, and integrating technology in teaching, the role of PAI teachers can be more optimal in fostering the practice of students' religious values.